Clear‐cutting triggers regeneration of abandoned secondary forests but risks alternative successional trajectories with high deer density. Issue 3 (21st July 2021) - Suzuki, Maki; Karukome, Tsutomu; Fujihira, Koji; Mitsugi, Mitsukazu; Hisamoto, Yoko
Abstract: Questions: Does clear‐cutting intended to boost regeneration of abandoned secondary forests lead to an irreversible shift to non‐forest vegetation under high deer density? Location: Warm‐temperate forests in Boso Peninsula, Chiba Prefecture, Japan. Methods: We designed a factorial experiment including two levels of forest canopy treatment (clear‐cutting or intact canopy) and two levels of herbivory control (presence or absence of deer) using 24 plots of 10 m × 10 m. Vegetation dynamics occurring under each experimental treatment were tracked for 7.5 years. Results: Ground vegetation under the closed canopy did not change significantly for 7.5 years both inside and outside the deer fences. However, plots were rapidly covered by early‐seral plants till 1.5 years after the cutting event. The quick growth of ground vegetation after clear‐cutting was supported by plants that are known to have soil seed banks, as suggested by their ubiquity immediately after clear‐cutting. Species richness of ground vegetation was maximized at that time and gradually decreased afterward, suggesting biological filtering. This filtering process worked differently inside and outside the deer fences, resulting in different types of vegetation. The clear‐cut‐and‐fence plots became dominated by tree recruits that will recover secondary forests in the future. Contrastingly, vegetation outside the fences lacked many species (e.g., common tree species) that were found inside the fences and became dominated by shrubs and plants unpalatable to deer. This post‐cutting vegetation outside the fences was not similar to that inside the deer fences at any seral stage. This means that the vegetation outside the fences could be tracking an alternative successional trajectory rather than a case of arrested succession. Conclusions: Here, abandoned secondary forests still seem to maintain a high regeneration potential that would be triggered by clear‐cutting, but reducing herbivory pressure by deer is necessary to avoid the risk of alternative successional trajectories. Abstract : A 7.5‐year experiment using combinations of clearcutting and deer exclusion (fencing) in Japanese secondary forests demonstrated the high regeneration potential of forests subject to cutting‐and‐fencing and the establishment of nonforest vegetation in cutting‐no‐fencing forests. The observed shift toward nonforest vegetation is more likely to represent an alternative succession trajectory rather than arrested succession, as suggested by species turnover analysis.